Stealth emulsion based on natural rubber latex, core-shell ferrofluid/carbon black in the S and X bands - Vinayasree, S.; Nair, Ajalesh Balachandran; Mani, Manoj; Archana, V. N.; Joseph, Rani; Mohanan, P.; Joy, P. A.; Anantharaman, M. R. (Nanotechnology, 2019)
A lossy dielectric with an appropriate magnetic property is one of the requirements of a stealth material. The thickness of the absorber and the corresponding bandwidth of absorption are also other deciding factors that determine the choice of the material as microwave absorbers. A stable emulsion, which is lossy as well as magnetic, is promising, since it can be coated on surfaces with required thickness in the desired band. A magnetic nanofluidic emulsion serves the purpose. A microwave absorbing emulsion based on natural rubber latex with core-shell magnetic nanoparticles, based on superparamagnetic iron oxide nanoparticles (SPIONs), was developed. The effect of additives like carbon black on the bandwidth of absorption was also studied as a function of weight percentage of carbon black. The complex dielectric permittivity and magnetic permeability were evaluated using a vector network analyser in the S and X bands. Furthermore, these results were modelled using surface impedance equations. These investigations revealed that the incorporation of carbon black enhances the bandwidth of absorption and an emulsion with the required dielectric permittivity and magnetic permeability can be tailored for stealth applications.
Keywords: carbon black; core-shell nanoparticles; ferrofluid; microwave absorbing paint; natural rubber latex